Rearrangement of allyl phenyl ether over Al-MCM-41 - Mathew, Nevin T.; Khaire, S.; Mayadevi, S.; Jha, Ratnesh Kumar; Sivasanker, S. (Journal of Catalysis, 2005)
Claisen rearrangement of allyl phenyl ether to o-allylphenol and a dihydrobenzofuran derivative was investigated over MCM-41 with different Si/Al ratios. Higher aluminum content, higher reaction temperatures, and longer run duration favor the formation of the ring compound 2,3-dihydro-2-methyl benzofuran. There is a close relationship between acidity and conversion, which suggests that the reaction occurs inside the large pores of MCM-41. The influence of temperature and catalyst Si/Al ratio on the reaction are examined by kinetic analysis, under the assumption of a first-order consecutive reaction. (C) 2004 Elsevier Inc. All rights reserved.
Keywords: Al-MCM-41; allyl phenyl ether; Claisen rearrangement; Mesoporous material; molecular rearrangement; Solid acids

Claisen rearrangement of allyl phenyl ether over zeolites beta, mordenite and Y - Wagholikar, S. G.; Mayadevi, S.; Jacob, Nalini E.; Sivasanker, S. (Microporous and Mesoporous Materials, 2006)
The Claisen rearrangement of allyl phenyl ether (APE) to o-allylphenol was investigated over zeolites beta (BEA), mordenite (MOR) and Y (FAU) with different Si/Al ratios. Over the zeolite catalysts, the allylphenol cyclized to produce 2,3-dihydro-2-methyl benzofuran. Larger catalyst loading, higher reaction temperatures and longer run duration favored the formation of the ring compound. Conversion was small over MOR and FAU although they possessed higher acidity (as measured by the temperature programmed desorption of ammonia) compared to BEA. Studies using BEA revealed that the nature of the solvent influenced the reaction rate. The order of reactivity in the solvents was, benzene > EDC (1,2-dichloroethane) > toluene > TCE (1, 1,2,2-tetrachloroethane) >> ACN (acetonitrile). The intermediate allylphenol reacted with the aromatic solvents to produce byproducts when benzene and toluene were used as solvents. A kinetic analysis assuming first order series and parallel reactions is presented. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: allyl phenyl ether; allylphenol; Benzofuran; Claisen rearrangement; zeolites

Cascade synthesis of dihydrobenzofuran via claisen rearrangement of allyl aryl ethers using FeCl 3 /MCM-41 catalyst - Sakate, Sachin S.; Shinde, Suhas H.; Kasar, Gayatri B.; Chikate, Rajeev C.; Rode, Chandrashekhar V. (Journal of Saudi Chemical Society, 2018)
Dihydrobenzofuran as one of the active ingredients of the naturally occurring motif is synthesized by using in situ generation of ortho allyl phenols. Aryl allyl ethers on reacting with catalytic amounts of non noble metal iron (III) chloride supported on MCM-41 under moderate reaction conditions yield dihydrobenzofuran. First step via Claisen rearrangement gives ortho allyl phenol followed by its in situ cyclization to yield dihydrobenzofuran in very good yields. Both Lewis as well as Brønsted acidity of the catalyst as evidenced by Py-FTIR studies was found to catalyze the cascade synthesis of dihydrobenzofuran. The scope of the present strategy was successfully demonstrated for several substrates with varying electronic effects for the synthesis of corresponding dihydrobenzofuran with high yields in a range of 71-86%.
Keywords: Aryl allyl ether; Claisen rearrangement; Dihydrobenzofuran; Ferric chloride; MCM-41

Rapid bioinspired N-acyliminium ion strategy for the ABC core of the stemona alkaloids - Chavan, Subhash P.; Kalbhor, Dinesh B.; Gonnade, Rajesh G. (Asian Journal of Organic Chemistry, 2023)
A concise and highly diastereoselective bioinspired key cationic cyclization strategy for the asymmetric synthesis of the tricyclic core of the (-)-stemoamide, together with 8,9-bis-epi-stemoamide has been described. The key N-acyliminium ion precursors were accessed from L-tartaric acid and L-malic acid respectively. The use of ethyl acetoacetate derived bifunctional allylidenetriphenylphosphorane reagent in the early stage of the synthetic strategy is advantageous for the rapid construction of highly functionalized key pyrrolo[1,2-& alpha;]azepine frameworks.
Keywords: alkaloids; Biomimetic synthesis; Claisen rearrangement; cyclization; Regioselectivity